2019
DOI: 10.1186/s40834-019-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting demand for modern contraceptives among currently married reproductive age women in rural Kebeles of Nunu Kumba district, Oromia, Ethiopia

Abstract: BackgroundFamily planning plays a key role in improving the health of the mother and the child. Yet there are still significant levels of demand for family planning that are unmet and these can lead to unintended pregnancy. So, women’s demand for contraceptive utilization to limit, space, or delay the number of family size can be increased by integrating family planning service at each service delivery points.ObjectiveThe main aim of this study was to assess the demand for modern contraceptive and associated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 9 publications
15
29
0
Order By: Relevance
“…Advances in Public Health e overall level of modern contraceptive use was consistent with studies done in Northwest Ethiopia (51.3%) [22] and Sudan (51.5%) [23]. However, it was lower compared to the study done in the Oromia region, Ethiopia, 55.7% [24], and western Ethiopia (71.9%) [25]. e reason for this variation might be the educational status and cultural difference of study participants.…”
Section: Discussionsupporting
confidence: 78%
“…Advances in Public Health e overall level of modern contraceptive use was consistent with studies done in Northwest Ethiopia (51.3%) [22] and Sudan (51.5%) [23]. However, it was lower compared to the study done in the Oromia region, Ethiopia, 55.7% [24], and western Ethiopia (71.9%) [25]. e reason for this variation might be the educational status and cultural difference of study participants.…”
Section: Discussionsupporting
confidence: 78%
“…This result could be likened to a study done by Haile and Fantahun [35], which showed women with 1-3 and 4-12 children were having fifty-one and six times higher demand than those who had no child respectively in Ethiopia. A recent study in the same country also found that women who had 2-3 children were almost three times more likely to have demand for modern methods of contraception than women who had no and one child [36]. In explaining the plausible reason accounting for this observation, Kebede, Abaya, Merdassa and Bekuma [36] contended that due to the more child the woman is having, the more likely she wants to space or limit the number of children and the more she was using contraceptives.…”
Section: Discussionmentioning
confidence: 92%
“…[16][17][18] In Ethiopia, this high unmet demand and other factors such as lack of awareness, fear of social rejection, resistance to spouses, religious or cultural values, and concern for contraceptive side-effects lead to a high fertility rate (average 4.6 children). [18][19][20][21] As mentioned in the SDGs, fostering a rapid reduction in fertility to or below the level of substitution is necessary in order to foster economic development. In reaction to these global goals, the Ethiopian Federal Ministry of Health (FMoH) set a target for a contraception prevalence rate of 55% by 2020.…”
Section: Introductionmentioning
confidence: 99%